Meningkatkan Psikospritual Perawat dengan Pengukuran Assesment of Sprituality and Religious Sentiments (Aspires) - Blasius Perang (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Psychosprituals are the integrative energy nurses need to serve patients. An empathetic nurse is a nurse who can develop psycho-spirituality, which is a need that must be met. Objective: To get a clear picture of nurses in psychospiritual aspects in several private hospitals in South Sulawesi. Method: This study is comparative analytical research with a cross-sectional multisite study approach. Results: showed that the psychospiritual level of nurses at several private hospitals in Makassar city was good. ASPIRES is categorized as good if you get a score>70; the category is sufficient if you get a score of 35–70 and categorized as less if the value is <35. Conclusion: There are significant psychospiritual differences in nurses based on demographic characteristics, namely gender, age, level of education, and length of service. It can be used as information material for hospitals to improve the quality of services by paying attention to psychospiritual aspects through programs offered by researchers